Health Literacy and Pre-Eclampsia Knowledge of Pregnant Mother in Primary Health Care in Surabaya - Daryan Alif Putra; Fundhy Sinar Ikrar Prihatanto; Pudji Lestari (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Background: Health literacy is defined as individual’s ability to gather, communicate, process, and understand basic health information and services to make appropriate health decision. The purpose of this study was to find the connection between health literacy and knowledge of pre-eclampsia in Surabaya. Methods: Data collection used pregnant women at their first and second trimester as its research subjects from August to September 2018. The study used modified SAHL-E test and modified questionnaire for knowledge of pre-eclampsia. Data processing used Chi square. Results: There was a significant relationship between health literacy and the knowledge of pre-eclampsia (p= 0.029). Conclusions: This study showed that there was a relationship between health literacy of the participants and their knowledge of Pre-eclampsia.